Awakening the management of coworking spaces - Bouncken, Ricarda B. (Emerald Publishing Limited, 2023)
Before 2019, coworking spaces were flourishing, however the COVID-19 pandemic put growth on hold. As organizations have begun to move towards more hybrid ways of working, they are becoming the preferred option and are particularly attractive for new business ventures. There are significant gaps in the research of coworking spaces: their forms, configurations, influences, challenges, and how to manage transformations of incumbents when establishing spaces. The trend is being noticed, but a better understanding of the phenomenon and a consideration of management innovations is needed to fully harness the true possibilities of coworking spaces. In Awakening the Management of Coworking Spaces, the chapter authors combine a scientific approach with managing implications, developing theoretic constructs, reporting qualitative and quantitative findings about challenges, potentials, effects, managerial solutions, and success stories. The contributors are academics and practitioners, bringing together their research and real-world experiences to help organizations shape best practices. An applicable and scholarly collection of chapters offers the latest research on coworking spaces - both the benefits and challenges - and provides a roadmap for corporations to get the best out of their employees whilst maximising their potential.